PENGARUH PUASA SENIN KAMIS TERHADAP KEDISIPLINAN SANTRI PUTRA PONDOK PESANTREN DARUL FALAH BANDUNG BARAT - Abdullah, Muhammad Muchlis Solehudin (Prodi Pendidikan Agama Islam STAI Darul Falah, 2023)
The purpose of this research is to determine the influence of fasting on Mondays and Thursdays on the discipline of male students at Darul Falah Islamic Boarding School. This research is quantitative in nature with a descriptive quantitative research design. The method used is a survey method, and the data collection technique utilized is a questionnaire. The results of this research show that the implementation of fasting on Mondays and Thursdays has a significant impact on the discipline of students at Darul Falah Islamic Boarding School. This is demonstrated by the regression equation 72.635 + 0.629X, a correlation coefficient of 0.629, and a determinant coefficient of 38%. Thus, fasting on Mondays and Thursdays has a 38% influence on the discipline of male students at Darul Falah Islamic Boarding School, while 62% is influenced by other factors not studied in this research. The obtained t-value > t-table, or 7.295 > 2.051, therefore, Ho is rejected and Ha is accepted, indicating significance. In conclusion, the discipline of male students is significantly influenced by fasting on Mondays and Thursdays. Therefore, it is hoped that this research will have a positive impact on the administrators in enhancing the discipline of male students at Darul Falah Islamic Boarding School in West Bandung.